Differentiated characteristics of coping strategies and defense mechanisms in individuals with varying levels of emotional stability - ANANOVA, Ivanna (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background. Coping strategies and defense mechanisms regulate behavior, enabling individuals to overcome challenging situations and mitigate the adverse effects of stressors. Emotional traits such as emotional stability, emotional balance, and neuroticism influence the selection of coping strategies and defense mechanisms. This study aimed to investigate how individuals with varying levels of emotional stability employ coping strategies and defense mechanisms. Methods. The methods employed included: 1. Empirical tools – questionnaires such as the Life Style Index by R. Plutchik, H. Kellerman, and H. Conte; the Ways of Coping Questionnaire by R. Lazarus and S. Folkman; and the Neuroticism Scale by H. Eysenck and G. Wilson. 2. Statistical techniques – Correlation Analysis; K-Means Cluster Analysis; One-Way ANOVA (with Kruskal–Wallis H test as a nonparametric alternative); and Post Hoc multiple comparisons tests, including Scheffé’s test (nonparametric alternative: Mann–Whitney U test). The sample comprised 178 individuals aged 20 to 35. Results. Findings indicated that emotionally stable individuals primarily use coping strategies such as planful problem solving, self-controlling, and the defense mechanism of denial. Conversely, emotionally unstable individuals tend to utilize coping strategies like escape-avoidance, accepting responsibility, and distancing, alongside defense mechanisms like regression, displacement, reaction formation, compensation, and projection. Six types of emotional stability, including neuroticism, were identified, each with distinct coping and defense patterns. A strong tendency toward self-deprecation was linked to defense mechanisms such as displacement and regression. In contrast, higher levels of obsessiveness correlated with the use of projection, reaction formation, and the coping strategy of positive reappraisal. Conclusions. The degree of emotional stability and the qualitative composition of emotional stability-neuroticism manifestations determine differences in the coping-defense repertoire. These findings reveal the differential nature of coping-defense responses and provide criteria for differentiating the constructiveness of coping-defense repertoires and individual manifestations of neuroticism.